Avaliação do potencial fisiológico de sementes de coentro pelo teste de envelhecimento acelerado - Pereira, Maria Francisca Soares (2012)
The evaluation of the vigor is of fundamental importance in control programs of seed quality, and accelerated aging test can be used for this purpose. In this sense, the objective of this paper was to study the methodology of the accelerated aging test, seeking to verify their efficiency to identify differences between levels of seed lots vigor of coriander (Coriandrum sativum L.). During the experimental period, the seeds were packed in plastic bags and kept in a controlled environment (16 ° C and 50% RH). For this, the following cultivars Verdão, Super-verdão, Tabocas and Portugues were used, each one represented by three lots. The seeds were tested for germination, first count germination, seedling emergence, speed of emergence, shoot length, dry mass of shoots and accelerated aging (38 and 41 ° C for 48, 72 and 96 hours; method traditional and with use of saline solution), besides the determination of moisture content of seeds. The work was performed at the Laboratory of Seed Analysis and in the greenhouse of the Universidade Federal Rural do Semi-Arido Mossoró-RN. A completely randomized design with four replications of 50 seeds was used. The test results were evaluated individually. The analysis of variance was performed by F test and the means compared by Tukey test (P ≤ 0.05). It was concluded that the accelerated aging test was efficient to evaluate the physiological potential of coriander seeds, and that combinations 41°C/48h (traditional method) and 41°C/72h (with saline solution) constituted in an efficient procedure to detect differences of vigor among seed lots of coriander